Response to Strona & Fattorini: are generalist parasites being lost from their hosts?. (11th January 2016) - Farrell, Maxwell J.; Stephens, Patrick R.; Davies, T. Jonathan
Abstract : We respond to criticism of our recent paper by examining assumptions about the structure of host‐parasite networks, and discuss the implications of host extinction on our perception of parasite specificity.